Scope and structure of German official development assistance: trends and implications for the BMZ and other ministries - Michael Bohnet; Stephan Klingebiel; Paul Marschall (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The structure of German Official Development Assistance (ODA) is in a state of transition. Germany's growing international role, the increasing importance of climate issues as well as the refugee crisis are contributing greatly to a significant increase in German ODA, which has more than doubled since 2012 and amounted to around EUR 22 billion in 2017. The coalition agreement between the CDU/CSU and the SPD in 2018 has prioritised ODA-eligible expenditures and views development policy as a priority area. Significant changes can also be seen with regard to the scope and pattern of ODA expenditures: The budget of the Federal Ministry for Economic Cooperation and Development (BMZ) and its share of the federal budget have increased due to an upvaluation of development cooperation (DC). At the same time, the BMZ's portion in Germany's overall ODA fell from 73 per cent in 1995 to 33 per cent in 2016. Nonetheless, projections for 2017 based on the second government draft for the 2018 budget indicate a trend reversal. Projection for 2017: BMZ 37 per cent, with KfW market funds 45 per cent; Federal Foreign Office (AA) 14 per cent; Projection for 2018: BMZ 49 per cent, with KfW market funds 53 per cent; AA 13 per cent. ODA-eligible contributions of other federal ministries have increased significantly. Both the ODA-eligible portion of the EU budget and the development policy contributions of the federal states have doubled since 1995. Market funds mobilised via the KfW as well as the eligible expenditures for refugees in Germany have been particularly important at times. The following interpretations can be drawn based on those trends: Largely positive interpretation from a development policy perspective: Development cooperation has become more important in recent years and is no longer a comparatively small area of activity that relates exclusively to the BMZ. New challenges have resulted from other ministries having a much stronger interest in maintaining and using resources for development cooperation. Germany's ODA contributions have thus risen overall and the BMZ's share of the budget has increased. Largely critical interpretation from a development policy perspective: The distribution of funds among a larger number of actors is making it difficult to pursue a coherent development policy approach, and other policy areas are not primarily aimed at development policy objectives due to their tasks and interests. The current situation implies a loss of importance for the BMZ and thus the original development policy area. Due to a rise in ODA contributions and the growing importance of a wide variety of development policy actors in Germany, there is now an increased need for greater coordination. The following is therefore recommended: conduct systematic development policy reviews of all ODA projects of all ministries more intensively coordinate Germany's ODA con¬tributions through the BMZ in a steering group concentrate ODA funds more towards the BMZ, which is the specialised department in development policy.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik